Small medium enterprises in food and beverage industry behavioural intention towards halal and fourth industrial revolution technology - Salme, Yahya; Mazita, Mokhtar (JOSSR, 2020)
The purpose of this study is to identify the impact of Small Medium Enterprises in Food and Beverage Industry Behavioural intention towards Halal and Fourth Industrial Revolution Technologies in Malaysia. This study is a quantitative descriptive study that uses questionnaires as a research instrument and uses unified theory of acceptance and use of technology (UTAUT) by Venkatesh, Morris, Davis, and Davis (2003) and theory of planned behaviour by Ajzen (1991) as a theoretical background. The expected findings of this study is there is a positive relationship in Halal and fourth industrial revolution technology acceptance toward small medium enterprises (SMEs) for food and beverage industries in Malaysia. Researchers view that there are some significant effects that may result from this study. However, it depends on the variables available and related to the present study